Roles of pyroptosis and immune infiltration in aortic dissection - Ge, Xiaogang; Cai, Qiqi; Cai, Yangyang; Mou, Caiguo; Fu, Junhui; Lin, Feng (Frontiers in Molecular Biosciences, 2024)
Aortic dissection (AD) commonly fatalities. Pyroptosis and immunological infiltration play a role in AD pathogenesis, but the molecular pathways linking immune infiltration and excessive inflammatory activation are unknown. We used two Gene Expression Omnibus datasets and a Gene Cards dataset of pyroptosis-related genes (PRGs) to research the pathogenic processes of immune infiltration and pyroptosis in AD. CIBERSORT was performed to evaluate immune infiltration in AD samples. We used univariate logistic regression, least absolute shrinkage, and selection operator regression to find AD diagnostic markers. We developed interaction networks using STRING and weighted gene correlation network analysis (WGCNA) to find important modules and essential genes. Single-sample gene set enrichment analysis determined immune infiltration, and Pearson correlation analysis assessed the association of key genes linked to AD with infiltrating immune cells. We found 31 PRGs associated with the inflammatory response, vascular epidermal growth factor receptor, and Rap1 signaling pathways. WGCNA found seven important genes for a critical module. CIBERSORT detected immune cell infiltration.Bioinformatics investigation revealed significant changes in immune cell infiltration and pyroptosis genes in AD and their connections. Key PRGs may be indicators for AD or high-risk individuals. Understanding AD pyroptosis and immune cell infiltration will lead to novel molecular targeted AD therapies.